Topographic Base Map Update in Nepal: Overview, Accomplishments and Way Forward - Baidar, Tina; Lama, Buddha; Gyawali, Rajeev; Pokhrel, Girija (Journal on Geoinformatics, Nepal, 2023)
The latest series of topographic base map of Nepal were prepared by Survey Department of Nepal during 1992-2001 A.D and preparation of their digital database namely National Topographic Database started in 1999 A.D. Understanding the utmost need of updating these maps and database, the department started update process in a rapid pace from fiscal year 2075/76 B.S based on ZiYuan-3 Survey and Mapping (ZY-3) satellite images with 2.1 m panchromatic and 5.8 m multispectral spatial resolution. The overall update procedure includes satellite image processing, feature update, field verification, field data compilation, finalization, map and database approval from Mapping Technical Subcommittee and finally map reproduction. The technical aspects of this whole process is based on standard specification document namely “Specifications for 1:25000 and 1:50000 Topographic Base Maps”. First level of update and field verification of all grid sheets covering Nepal was completed by fiscal year 2078/79 and is now in the phase of approval by Mapping Technical Subcommittee and reproduction. At the end of 2079 B.S, around 250 number of sheets have been approved and are made available by the department. With the completion of this update series, there are further opportunities to produce thematic data/maps as well as administrative maps of smaller scales. Furthermore, with the availability of higher resolution images through LiDAR, UAV and other resources, the department has opportunities to work on large scale mapping in coming days.